Derrida and the "Death of God" - Calano, Mark Joseph T. (Archīum Ateneo, 2024)
Jacques Derrida’s understanding of the death of God is rooted in but goes beyond Nietzsche’s and Hegel’s understanding of the concept. On the one hand, Nietzsche’s view of the death of God is related to two concepts: a closing horizon (which is the death of God) and an emerging horizon (which is the eternal recurrence); on the other hand, Hegel understands the death of God as the Absolute’s confrontation with its negation (death), and Aufhebung (the negation of negation). While Derrida’s notion of the death of God cannot be reduced simply to either a Nietzschean or Hegelian interpretation, it draws heavily from Nietzsche’s eternal recurrence and Hegel’s Aufhebung. This paper discusses how, for Derrida, a simple denial or negation of God is never accomplished because it leaves behind an evacuated and empty space, which opens up the possibility for a more complicated notion of the death of God. This complicated death of God consists in an undecidable play between life/death understood correctly in relation to différance and the trace, to mourning and sacrifice.